The MMS Dayside Magnetic Reconnection Locations During Phase 1 and Their Relation to the Predictions of the Maximum Magnetic Shear Model. Issue 12 (7th December 2017) - Trattner, K. J.; Burch, J. L.; Ergun, R.; Eriksson, S.; Fuselier, S. A.; Giles, B. L.; Gomez, R. G.; Grimes, E. W.; Lewis, W. S.; Mauk, B.; Petrinec, S. M.; Russell, C. T.; et al.
Abstract: Several studies have validated the accuracy of the maximum magnetic shear model to predict the location of the reconnection site at the dayside magnetopause. These studies found agreement between model and observations for 74% to 88% of events examined. It should be noted that, of the anomalous events that failed the prediction of the model, 72% shared a very specific parameter range. These events occurred around equinox for an interplanetary magnetic field (IMF) clock angle of about 240°. This study investigates if this remarkable grouping of events is also present in data from the recently launched MMS. The MMS magnetopause encounter database from the first dayside phase of the mission includes about 4, 500 full and partial magnetopause crossings and flux transfer events. We use the known reconnection line signature of switching accelerated ion beams in the magnetopause boundary layer to identify encounters with the reconnection region and identify 302 events during phase 1a when the spacecraft are at reconnection sites. These confirmed reconnection locations are compared with the predicted location from the maximum magnetic shear model and revealed an 80% agreement. The study also revealed the existence of anomalous cases as mentioned in an earlier study. The anomalies are concentrated for times around the equinoxes together with IMF clock angles around 140° and 240°. Another group of anomalies for the same clock angle ranges was found during December events. Key Points: The maximum magnetic shear model predicts magnetic reconnection at the Earth's magnetopause 80% accurate Anomalies in the predicting ability known from earlier studies have been confirmed The anomalies in predicting the reconnection location concentrate on Equinox and IMF clock angles of 120° and 240°